Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae) - Vas, Zoltán; Schwarz, Martin (Zootaxa, 2018)
Three species of Thaumatogelis Schwarz, 1995 are described as new: T. megaera Vas sp. nov. from Mongolia, T. alecto Vas sp. nov. from Jordan, and T. tisiphone Vas & Schwarz sp. nov. from Sicily, Italy. The identity of the previously misinterpreted T. pilosus (Capron, 1888) is clarified, and is redescribed. An updated identification key to the females of all known Thaumatogelis species is provided. Twelve new records from six countries are reported, some of them significantly expanding the known geographical distribution of certain Thaumatogelis species and that of the genus in the Palaearctic region.